Implementation of Think Pair and Share (TPS) Technique in Listening to Short Story Texts Learning - Ilma Rahim; Azis, Abdul; Ita Rosvita; Sri Asrawati Paramita (Jurnal Onoma: Pendidikan, Bahasa, dan Sastra, 2024)
This research aims to determine whether there are differences in students' abilities in listening to short story texts using the Think-Pair-Share (TTPS) cooperative learning method. Conducted as a quasi-experimental study, the sample comprised 11th-grade students from SMA DDI Maros. Data collection involved text analysis techniques, and the obtained data were analyzed through stages including the creation of raw score lists, frequency distributions, descriptive statistical analysis, and inferential statistical analysis. The results indicate significant differences in learning outcomes between students using the TTPS method and those not using it. The use of TTPS improved students' listening comprehension of short story texts, as evidenced by the mean score of 74.36 (high category) in the experimental class compared to 58.46 (low category) in the control class. This demonstrates that the TTPS method effectively enhances students' listening skills.